2021
DOI: 10.3389/fpubh.2021.692089
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional Study on Health Literacy and Internet Accessibility Among Patients With DM in Gansu, China

Abstract: Objective: To determine the relationship between the health literacy of patients with diabetes mellitus (DM) and the accessibility of internet surfing for information concerning DM.Methods: A multistage stratified sampling method was utilized to conduct a questionnaire survey on DM health literacy and internet accessibility among 1,563 patients with DM in Gansu Province in 2020. Logistic regression was performed to analyze the factors that influence health literacy and internet accessibility; while the chi-squ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…As the Internet continues to become more accessible globally, this disparity gap will close. [28][29][30]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the Internet continues to become more accessible globally, this disparity gap will close. [28][29][30]…”
Section: Discussionmentioning
confidence: 99%
“…This difference may also highlight a health literacy gap between Western and non-Western countries. As the Internet continues to become more accessible globally, this disparity gap will close 28–30 …”
Section: Discussionmentioning
confidence: 99%
“…In terms of age, researchers have reported that health literacy changes dynamically with age; the cognition of health-related information of the elderly declines year by year [ 30 ]. As for education level, it is mentioned that a person with higher education level is more capable of finding, understanding, and judging health-related information and interacting with health providers [ 31 , 32 ]. Moreover, considerable differences in economy, education, and geography between urban and rural areas may be the barrier for the elderly to utilize health-related resources [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Three studies on diabetes HL in China indicated that low socioeconomic status, low education, and no history of hyperglycemia were the main contributing factors for low diabetes HL among the elderly with prediabetes, living in rural areas, and diabetes patients. [114][115][116] Lower diabetes and high blood pressure HL were associated with poorer health outcomes or health-related quality of life. 115,117,114 China was the only country noted to survey infectious disease-specific HL among residents 15 years old and above.…”
Section: Main Outcomes Of Hl Studies In Asiamentioning
confidence: 99%